2016
DOI: 10.1021/acs.biomac.5b01750
|View full text |Cite
|
Sign up to set email alerts
|

Surface Morphology of Vapor-Deposited Chitosan: Evidence of Solid-State Dewetting during the Formation of Biopolymer Films

Abstract: Chitosan is a useful and versatile biopolymer with several industrial and biological applications. Whereas its physical and physicochemical bulk properties have been explored quite intensively in the past, there is a lack of studies regarding the morphology and growth mechanisms of thin films of this biopolymer. Of particular interest for applications in bionanotechnology are ultrathin films with thicknesses under 500 Å. Here, we present a study of thin chitosan films prepared in a dry process using physical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…During the phospholipid deposition process in high vacuum, the variation of the absolute ellipsometric polarizer angle P of the sample was measured using an electronic feedback loop connected to a Faraday rotator. This polarizer angle (P) increases during the deposition process with respect to an initial clean angle P 0 ~47°, with a fixed analyser angle A 0 ~20°, as described in [ 31 ]. The layer thickness is then calculated using the Drude model for single layers by relating the polarizer (P) and analyser (A) angles to the ellipsometric parameters Δ = 2P + 90° and ψ = A [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the phospholipid deposition process in high vacuum, the variation of the absolute ellipsometric polarizer angle P of the sample was measured using an electronic feedback loop connected to a Faraday rotator. This polarizer angle (P) increases during the deposition process with respect to an initial clean angle P 0 ~47°, with a fixed analyser angle A 0 ~20°, as described in [ 31 ]. The layer thickness is then calculated using the Drude model for single layers by relating the polarizer (P) and analyser (A) angles to the ellipsometric parameters Δ = 2P + 90° and ψ = A [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although promising, some drawbacks of the CH cushion arise due to its dynamics during evaporation. In particular, Retamal et al showed, in a separate work, that vapor deposited CH exhibits a solid-state dewetting processes on silicon surfaces that occurs during the evaporation at room temperature [ 31 ]. Recently, Cisternas et al, reported the vapor deposition of phospholipids on a different biocompatible substrate, titanium (Ti) [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the synthesis, polymethacrylic acid was deposited on a morpho butterfly wing template [ 16 ]. To date, inspired by nature, the specifically designed photonic crystals based on chitosan nanofibrils can respond to organic solvent or moisture [ 20 , 21 , 22 ]. Similar to chitosan-based nanostructures, self-assembled peptide nanostructures possess unique physical and biological properties and have broad application prospects in the field of electronic devices and functional molecular recognition [ 23 ].…”
Section: Introductionmentioning
confidence: 99%